2015
DOI: 10.1097/sle.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Splenectomy in Patients With Spleen Injuries

Abstract: Laparoscopic splenectomy is a safe feasible operation in patients with spleen injury. The operation is indicated in patients with spleen laceration >3 cm of parenchymal depth with moderate continuing bleeding or expanding hematoma and contraindicated in patients with hemodynamic instability and high bleeding rate (>500 mL/h on serial ultrasound examinations).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…According to the AAST criteria, our overall splenic grade approached IV. 14 Ermolov et al 12 reported a large study in 2015, comparing 23 laparoscopic splenectomies and 19 open splenectomies for grade III lacerations. The results showed longer operating times in the laparoscopic group, but no difference in complications or mortality, which is similar to the current investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the AAST criteria, our overall splenic grade approached IV. 14 Ermolov et al 12 reported a large study in 2015, comparing 23 laparoscopic splenectomies and 19 open splenectomies for grade III lacerations. The results showed longer operating times in the laparoscopic group, but no difference in complications or mortality, which is similar to the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…710 For more than 20 years, laparoscopic splenectomies in trauma patients have been described mostly in case reports or case series. 46,1113 However, the laparoscopic approach requires further investigation, because its role in trauma remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…1 demonstrate that laparoscopic splenectomy with selective ligation of hilar vessels is feasible and safe in selected patients with high-grade splenic trauma. Laparoscopy has several advantages over an open approach, such as more rapid postoperative recovery, reduced pain, wound and chest infections and a lower incidence of incisional hernias [2][3][4]. The reduced rate of chest infection associated with laparoscopic procedures is particularly important in trauma patients with lung contusions and rib fractures.…”
Section: Supporting Informationmentioning
confidence: 99%
“…For grades IV and V, non-operative management is associated with complications and higher failure rate [10]. The only steady condition mentioned in the literature in the choice of laparoscopic splenectomy for spleen lesions is that the patient should be hemodynamically stable [1,3,4,6,11]. On the other hand, asplenia increases the risk of serious infections and thromboembolic accidents and favors the progression of the atherosclerosis and the pulmonary hypertension [12] which has led surgeons from everywhere to try to preserve the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The management of the spleen trauma has evolved considerably however from exploratory laparatomy with splenectomy, to nonoperative management, partial splenectomy and laparoscopic splenectomy. There is more and more reporting of the minimally invasive approach to spleen trauma and although laparoscopic splenectomy in trauma requires a longer time of surgery [3], patients benefit from all the advantages of this procedure. Splenomegaly was considered the open surgery privilege but with the evolution of surgeons' experience and that of the equipment, the indication of laparoscopic splenectomy expanded to splenomegaly of up to 1000 g or maximum size of 15 cm [4].…”
Section: Introductionmentioning
confidence: 99%